Investigation of the Strength Properties of Palm Kernel Shell Ash Concrete - Olutoge, F. A.; Quadri, H. A.; Olafusi, O. S. (Engineering, Technology & Applied Science Research, 2012)
Many researchers have studied the use of agro-waste ashes as constituents in concrete. These agro-waste ashes are siliceous or aluminosiliceous materials that, in finely divided form and in the presence of moisture, chemically react with the calcium hydroxide released by the hydration of Portland cement to form calcium silicate hydrate and other cementitious compounds. Palm kernel shell ash (PKSA) is a by-product in palm oil mills. This ash has pozzolanic properties that enables it as a partial replacement for cement but also plays an important role in the strength and durability of concrete. The use of palm kernel shell ash (PKSA) as a partial replacement for cement in concrete is investigated. The objective of this paper is to alleviate the increasing challenges of scarcity and high cost of construction materials used by the construction industry in Nigeria and Africa in general, by reducing the volume of cement usage in concrete works. Collected PKSA was dried and sieved through a 45um sieve. The fineness of the PKSA was checked by sieving through 45um sieve. The chemical properties of the ash are examined whereas physical and mechanical properties of varying percentage of PKSA cement concrete and 100% cement concrete of mix 1:2:4 and 0.5 water-cement ratios are examined and compared. A total of 72 concrete cubes of size 150 × 150 × 150 mm³ with different volume percentages of PKSA to Portland cement in the order 0:100, 10:90 and 30:70 and mix ratio of 1:2:4 were cast and their physical and mechanical properties were tested at 7, 14, 21 and 28 days time. Although the compressive strength of PKSA concrete did not exceed that of OPC, compressive strength tests showed that 10% of the PKSA in replacement for cement was 22.8 N/mm2 at 28 days; which was quite satisfactory with no compromise in compressive strength requirements for concrete mix ratios 1:2:4. This research showed that the use of PKSA as a partial replacement for cement in concrete, at lower volume of replacement, will enhance the reduction of cement usage in concretes, thereby reducing the production cost. This research was carried out at the University of Ibadan, Ibadan, Nigeria.